2006
DOI: 10.1677/jme.1.02061
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reduces lipolysis in primary rat adipocytes stimulated by tumor necrosis factor-α or isoproterenol

Abstract: In patients with type 2 non-insulin-dependent diabetes mellitus (NIDDM), the biguanide, metformin, exerts its antihyperglycemic effect by improving insulin sensitivity, which is associated with decreased level of circulating free fatty acids (FFA). The flux of FFA and glycerol from adipose tissue to the blood stream primarily depends on the lipolysis of triacylglycerols in the adipocytes. Adipocyte lipolysis is physiologically stimulated by catecholamine hormones. Tumor necrosis factor-a (TNF-a), a cytokine la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 37 publications
3
48
0
2
Order By: Relevance
“…8 In addition, TNFa stimulates lipolysis in adipocytes. 16 Hence, increased TNFa expression in mesenteric WAT may have promoted FFA release in HFD RF mice. Such effect may be limited to the mesenteric fat depot since short-term HFD did not affect lipolytic function of systemically drained epididymal WAT.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, TNFa stimulates lipolysis in adipocytes. 16 Hence, increased TNFa expression in mesenteric WAT may have promoted FFA release in HFD RF mice. Such effect may be limited to the mesenteric fat depot since short-term HFD did not affect lipolytic function of systemically drained epididymal WAT.…”
Section: Discussionmentioning
confidence: 99%
“…The positive influence of different drugs, such as metformin, thiazolidinediones, and salicylates, on NAFLD has been related, at least in part, to their modulation of peripheral lipolysis (Ren et al, 2006). In particular, thiazolidinediones and salicylates are thought to reduce TNF-␣-induced lipolysis, the latter of which potentially involves a mechanism that prevents reduction of perilipin A (Souza et al, 1998;Zu et al, 2008).…”
Section: Novel Targets For Therapeutic Intervention In Nonalcoholimentioning
confidence: 99%
“…47 Treatment of adipocytes with metformin could attenuate TNF-a-mediated lipolysis by suppressing phosphorylation of ERK1/2 and reverse the down-regulation of perilipin protein. 48 Another study indicated that TNF-ainduced lipolysis by blunting endogenous inhibition of lipolysis and Gi protein down-regulation might also be involved. 49 However, results from subcutaneous administration of a polyclonal goat anti-rat TNF antibody to Zucker rats revealed that anti-TNF treatment could not alter lipid metabolism in the obese animals.…”
Section: Tnf-a Induces Lipolysismentioning
confidence: 99%